Biopolymer chitosan: potential sources, extraction methods, and emerging applications - Hisham, Firzanah; Mohd Hatta, Maziati Akmal; Ahmad, Farah; Ahmad, Kartini; Samat, Noorasikin (Elsevier, 2024)
Food manufacturing generates a considerable amount of leftovers. Garbage disposal could cause environmental and ecological issues. Nevertheless, it is often possible to convert waste into high-value usable goods. Researchers have combed through natural wastes and discovered substances that could be re-utilised to address the issues. One of the materials discovered in marine waste is chitin, which could be transformed into chitosan. Chitosan is a natural biopolymer derived from chitin, which is non-toxic, biodegradable, and biocompatible. Therefore, chitosan has a wide range of possible applications. Moreover, chitosan has been widely acknowledged to be an effective biomaterial in a variety of ways. This review aims to examine more closely the primary sources of chitosan, extraction methods, and applications.